Assesment of Thermodynamic Irreversibility in a Micro-Scale Viscous Dissipative Circular Couette Flow - Pranab Kumar Mondal; Somchai Wonwises (Entropy, 2018)
We investigate the effect of viscous dissipation on the thermal transport characteristics of heat and its consequence in terms of the entropy-generation rate in a circular Couette flow. We consider the flow of a Newtonian fluid through a narrow annular space between two asymmetrically-heated concentric micro-cylinders where the inner cylinder is rotating at a constant speed. Employing an analytical methodology, we demonstrate the temperature distribution and its consequential effects on the heat-transfer and entropy-generation behaviour in the annulus. We bring out the momentous effect of viscous dissipation on the underlying transport of heat as modulated by the degree of thermal asymmetries. Our results also show that the variation of the Nusselt number exhibits an unbounded swing for some values of the Brinkman number and degrees of asymmetrical wall heating. We explain the appearance of unbounded swing on the variation of the Nusselt number from the energy balance in the flow field as well as from the second law of thermodynamics. We believe that the insights obtained from the present analysis may improve the design of micro-rotating devices/systems.